Business strategies and performance of ceramics manufacturing firms in Thailand - Seedee, Rattana; Sulaiman, Mohamed; Ismail, Ishak (2009)

(untitled)
This study reports the results of research on business strategies of Thai ceramics manufacturing firms in an attempt to answer two questions. First, what overall competitive business strategies are being employed by Thai ceramics firms? Second, do these strategies contribute to performance? Porter’s concept of generic strategies is used as business strategy variables. Data were collected from 141 ceramics firms in Thailand. The data show significant relationship between business strategies and firm performance. Both low cost leadership and differentiation strategies were found to have significant relationship with firm performance. However, low cost leadership was shown to have higher profits than differentiation strategy. The paper also discusses the implications and limitations of the study.